Knowledge, use and performance of the organizational communication planning and measurement tools among communicators working at companies of five economic sectors in Medellin, Colombia - Berrío Bedoya, Elízabeth; Ramírez Jaramillo, Karen; Ocampo Arroyave, Mariana; Hernández García, David (Folios, revista de la Facultad de Comunicaciones y Filología, 2011)
The organizational communication has adopted and adapted management tolos to its field such as strategic planning and communication indicators: planning and measurement tools which opérate under the communication functionalist model since that they contribute to the normalization and formalization of the communication management elements: objetives, strategies, receivers, messages, channels, reponsible officers indicators. Among others; it is throughout the formulation and applications to the achievement of the organization strategic objectives are measured and projected. The following paper illutrates the results obtained in the research process aimed at determining the degree of knowledge, use and follow up of the organizational communication planning and measurement tools among communicators working at big companies belonging to the services, food and beverages, comercial, cultural or educational sectors in Medellin. Colombia. The conclusión reached is that the plannig tools for the organizational communication, compared to the measurement tools, are far more known, used, and which are subject, by the communicators involved in this research, to more follow up processes.